1999
DOI: 10.2139/ssrn.145530
|View full text |Cite
|
Sign up to set email alerts
|

Solving Two Production Scheduling Problems with Sequence-Dependent Set-Up Times

Abstract: In today's competitive markets, the importance of good scheduling strategies in manufacturing companies lead to the need of developing efficient methods to solve complex scheduling problems.In this paper, we studied two production scheduling problems with sequence-dependent setups times. The setup times are one of the most common complications in scheduling problems, and are usually associated with cleaning operations and changing tools and shapes in machines.The first problem considered is a single-machine sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…We have shown that some fundamental dominance properties are lost when considering simple extensions of the nondelay and Giffler-Thompson SGSs based on operation appending to sequence-dependent setup times, as performed by most previous studies on priority rule-based heuristics for the SDST-JSP in the literature, e.g. Allahverdi, Gupta and Aldowaisan (1999) [11] Kim and Bobrowski (1994), [14] and Ovacik and Uzsoy (1994). On the other hand, we have demonstrated that the serial algorithm based on operation insertion (Kolisch (1996)) has the ability to generate a dominant set of schedules.…”
Section: Discussionmentioning
confidence: 68%
“…We have shown that some fundamental dominance properties are lost when considering simple extensions of the nondelay and Giffler-Thompson SGSs based on operation appending to sequence-dependent setup times, as performed by most previous studies on priority rule-based heuristics for the SDST-JSP in the literature, e.g. Allahverdi, Gupta and Aldowaisan (1999) [11] Kim and Bobrowski (1994), [14] and Ovacik and Uzsoy (1994). On the other hand, we have demonstrated that the serial algorithm based on operation insertion (Kolisch (1996)) has the ability to generate a dominant set of schedules.…”
Section: Discussionmentioning
confidence: 68%
“…Kim and Bobrowski (1994) extend the preceding work to various performance measures and propose compound priority rules. Noivo and Ramalhinho-Lourenço (1998) propose also new priority-rules considering setup times and compare them with classical priority-rules. Ovacik and Uzsoy (1994a) propose a more sophisticated priority-rule based algorithm for problem J |s ij |L max with reentrant jobs (a job may use a machine more than once).…”
Section: Priority-rule Based Methodsmentioning
confidence: 99%
“…They propose a priority rule which aims at selecting the job yielding the smallest setup time when a machine becomes available. Later, Kim and Bobrowski (1994) consider various performance measures and propose compound priority rules; and Noivo and Ramalhinho-Lourenço (1998) propose new priority rules and compare with previous ones. Brucker and Thiele (1996) propose a priority rule as an extension of the G&T algorithm (Giffler and Thomson 1960).…”
Section: Priority Rulesmentioning
confidence: 99%